Analisis Konsep Pendidikan Karakter dalam QS. Al-Ahzab Ayat 21: Perspektif Tafsir Al-Misbah dan Implementasinya dalam Pendidikan Islam Kontemporer - Wagola, Rajun; Arqom, Mhd. Lailan; Waharjani (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Character education is a fundamental aspect in shaping students’ personalities, especially amid the moral challenges of contemporary society. This study aims to analyze the concept of character education in the Qur’anic verse Al-Ahzab 33:21 based on the interpretation of Tafsir Al-Misbah and to explore its relevance and implementation in contemporary Islamic education. This research employs a qualitative approach using library research and content analysis of primary and secondary sources. The findings reveal that the concept of uswah hasanah in the verse emphasizes the exemplary conduct of Prophet Muhammad as the primary model for character formation, encompassing integrity, responsibility, patience, and social ethics. Tafsir Al-Misbah highlights the importance of practical exemplification in the internalization of values. The implementation of this concept in contemporary Islamic education can be realized through strengthening character-based curricula, teacher exemplarity, and the cultivation of digital ethics. This study affirms the relevance of prophetic values in addressing modern educational challenges.